Erratum to: The management of intra-abdominal infections from a global perspective: 2017 WSES guidelines for management of intra-abdominal infections - Massimo Sartelli; Alain Chichom‐Mefire; Francesco M. Labricciosa; Timothy Craig Hardcastle; Fikri M. Abu‐Zidan; A. R. K. Adesunkanmi; Luca Ansaloni; Miklosh Bala; Zsolt J. Balogh; Marcelo A. Beltrán; Offir Ben‐Ishay; Walt Biffl; et al. (2017)
[This corrects the article DOI: 10.1186/s13017-017-0141-6.].